PENGEMBANGAN KARAKTER DALAM OLAHRAGA DAN PENDIDIKAN JASMANI - Sri Winarni (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: Character Development in Sports and Physical Education. There are three approaches to character development, i.e. the social learning, structural development, and socio-psychological approaches. These underlie nine strategies to develop character through physical and sports activities. The strategies can be implemented by formulating characteristics of real sportspeople in a program, strengthening sportsmanlike behaviors, modeling good and appropriate behaviors, explaining why particular behaviors are good and acceptable, discussing moral dilemmas, actualize moral dilemmas in actual situations, teaching cooperative learning strategies, creating an atmosphere that motivates movement tasks, and transferring power from leaders to participants (members). Keywords: character development, sports, physical education